Using transgenic reporters to visualize bone and cartilage signaling during development in vivo - Hammond, Chrissy L.; Moro, Enrico (Frontiers in Endocrinology, 2012)
Green Fluorescent Protein (GFP) was first used as a marker of protein expression in vivo 18 years ago, heralding the beginning of what became known as the Green Revolution. Since then, there has been an explosion in the number of transgenic lines in existence, and these transgenic tools are now being applied to skeletal research. Advances in transgenesis are also leading to increasing use of new model organisms for studying skeletogenesis. Such new models include the small teleosts zebrafish and medaka, which due to their optical translucency offer imaging possibilities in the live animals. In this review, we will introduce a number of recent advances in genetic engineering and transgenesis and the new genetic tools that are currently being developed. We will provide examples of how zebrafish and medaka transgenic lines are helping us to understand the behaviour of skeletal cells in vivo. Finally, we will discuss future prospects for the application of transgenic technology to skeletal research.